2014
DOI: 10.1002/2013jd021161
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and air pollution at mountain and plain stations in northern China: Insights gained from observations and modeling

Abstract: We analyzed 40 year data sets of daily average visibility (a proxy for surface aerosol concentration) and hourly precipitation at seven weather stations, including three stations located on the Taihang Mountains, during the summertime in northern China. There was no significant trend in summertime total precipitation at almost all stations. However, light rain decreased, whereas heavy rain increased as visibility decreased over the period studied. The decrease in light rain was seen in both orographic-forced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 72 publications
1
48
0
1
Order By: Relevance
“…At the same time, the inhibition of light precipitation by aerosols has also been reported in different regions of the world (Kaufman and Fraser, 1997;Rosenfeld and Lensky, 1998;Rosenfeld and 35 Givati, 2006;Wang et al, 2011;Guo et al, 2014). The invigoration theory was recently generalized by Fan et al (2018) that can also occur for shallower water clouds under extreme clean conditions under which ultra-fine mode aerosol particles may be nucleated to release latent heat to fuel cloud development.…”
Section: Introduction 25mentioning
confidence: 89%
See 1 more Smart Citation
“…At the same time, the inhibition of light precipitation by aerosols has also been reported in different regions of the world (Kaufman and Fraser, 1997;Rosenfeld and Lensky, 1998;Rosenfeld and 35 Givati, 2006;Wang et al, 2011;Guo et al, 2014). The invigoration theory was recently generalized by Fan et al (2018) that can also occur for shallower water clouds under extreme clean conditions under which ultra-fine mode aerosol particles may be nucleated to release latent heat to fuel cloud development.…”
Section: Introduction 25mentioning
confidence: 89%
“…Aerosol microphysical and radiative effects on precipitation usually interact and sometimes cancel each other out, leading to either invigoration or suppression 30 (Rosenfeld, 2000;Zhang et al, 2007;Rosenfeld et al, 2008), with both effects being found from such long-term measurements as the ARM (Li et al, 2011). Aerosols have an invigorative or suppressive effect depending on various factors, such as wind shear, humidity, cloud water amount, precipitation intensity (Fan et al, 2009;Li et al, 2011;Guo et al, 2014). (Zipser, 1994).…”
Section: The Vertical Structure Of Precipitation Associated With Aeromentioning
confidence: 99%
“…Therefore, great effort has been devoted to studying the air quality issue in this region (Guo et al, 2009(Guo et al, , 2011Zhao et al, 2009). Most of the previous studies have focused on the atmospheric chemistry and physics of air pollutants (Huang et al, 2014;Xia et al, 2007) and meteorological conditions in this region (Chen et al, 2009;Hu et al, 2014;Guo et al, 2014;Miao et al, 2015;Ye et al, 2015). Only a few studies (e.g., Streets et al, 2007;Wang et al, 2010) investigated how the emission control measures taken in Beijing affected the local air quality during the 29th Olympic Games in the summer of 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Through the IN effect, Fan et al (2014) and Muhlbauer and Lohmann (2009) found increased precipitation through enhanced snow formation. Enhanced orographic precipitation associated with dust particles that serve as IN to enhance ice formation is supported by observations in the western United States (Ault et al 2011;Creamean et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For orographic clouds and precipitation, many past studies suggested that aerosols could reduce precipitation or change the spatial distribution of precipitation through the CCN effect (Lynn et al 2007;Saleeby et al 2009;Rosenfeld et al 2007;Givati and Rosenfeld 2004;Jirak and Cotton 2006;Muhlbauer and Lohmann 2008;Saleeby et al 2013;Guo et al 2014;Xiao et al 2014). Through the IN effect, Fan et al (2014) and Muhlbauer and Lohmann (2009) found increased precipitation through enhanced snow formation.…”
Section: Introductionmentioning
confidence: 99%